Nasopharyngeal melanoma treated with radiotherapy - Nawrocki, Sergiusz; Radkowski, Andrzej; Górzyński, Michał; Iżycki, Dariusz (Contemporary Oncology/Współczesna Onkologia, 2006)
Primary mucosal melanoma of head and neck should be treated surgically with optional adjuvant radiotherapy according to several authors. We have treated unoperable nasopharyngeal melanoma with 3D teletherapy (70Gy/2Gy/7weeks) with boost from brachytherapy (9Gy/3Gy). Local control was achieved with acceptable acute and late toxicity (1-year follow-up), however, the patient died due to metastases to the central nervous system.